Diseminacion de la bacteriosis del palmito de pejibaye (Bactris gasipaes Kunth) - Mora Urpi, J.=700 1 Arroyo Oquendo, C.; Mexzon Vargas, R.; Bogantes Arias, A.
(Es, En)
Ilus., 15 ref.
Keywords: BACTERIOSIS; BACTRIS GASIPAES; METAMASIUS; PALMITOS; FUSARIUM; COSTA RICA; PANTOEA STEWARTII; METAMASIUS HEMIPTERUS; AGRONOMIA MESOAMERICANA